ВОПРОСЫ ОРГАНИЗАЦИИ ПСИХОЛОГИЧЕСКОЙ СЛУЖБЫ В ПЕРИНАТОЛОГИИ И РОДОВСПОМОЖЕНИИ - Нарметова, Ю. (SCIENCE and SOCIETY, 2016)
In the article the questions of the organization of psychological service in perinatology and obstetrics have been studied. Discussing the main problems of perinatal psychology, specialist‘s focuse their attention on the improvement of psycho-diagnostics and correction, as well as providing specialized psychological support to pregnant women. It was empha sized that the organization of psychological service in this sphere should suit to current research course, emphasizing the importance of the perinatal period in the further development of the psyche and personality, and it is aimed at studying psychological foundations of organization of behaviour during pregnancy, which will let represent the conditions of psychological well-being of women in this period and the successful development of their future children.